Collection and Evaluation of Genetic Diversity and Population Structure of Potato Landraces and Varieties in China - Wang, Ying; Rashid, Muhammad Abdul Rehman; Li, Xianping; Yao, Chunguang; Lu, Lili; Bai, Jianming; Li, Yanshan; Xu, Ningsheng; Yang, Qiongfen; Zhang, Linhai; Bryan, Glenn J.; Sui, Qijun; et al. (Frontiers in Plant Science, 2019)
China is the world’s leading country for potato production but potato is not native to China. To gain insights into the genetic diversity of potato germplasm various studies have been performed but no study has been reported for potato land-races in China. To improve the available genepool for future potato breeding programs, a diverse population containing 292 genotypes (including foreign elite lines, local landraces and cultivars) was developed and genotyped using 30 SSR markers covering the entire potato genome. A total of 174 alleles were detected with an average of 5.5 alleles per locus. The model-based structure analysis discriminated the population into two main sub-groups, which can be further subdivided into seven groups. One sub-group (P1) revealed less genetic diversity than other (P2) and contained a higher number of commercial cultivars possibly indicating a slight reduction in diversity due to selection in breeding programs. The P2 sub-group showed a wider range of genetic diversity with more new and unique alleles attained from wild relatives. The potato landraces, clustered in sub-population P1 may be derived from historical population imported from ancient European and International Potato Center genotypes while sub-population P2 may be derived from modern populations from International Potato center and European genotypes. It is proposed that in the first step, the potato genotypes were introduced from Europe to China, domesticated as landraces, and then hybridized for modern breeding.